3D graphene aerogel supported FeNi-P derived from electroactive nickel hexacyanoferrate as efficient oxygen evolution catalyst. (1st December 2018) - Narendra Kumar, Alam Venugopal; Li, Yinghao; Yu, Hongjie; Yin, Shuli; Xue, Hairong; Xu, You; Li, Xiaonian; Wang, Hongjing; Wang, Liang
Abstract: It is essential to design an oxygen evolution reaction (OER) electrocatalyst with smaller overpotential to improve water electrolyzer efficiency. Here, we report a simple method to incorporate nickel hexacyanoferrate into the three-dimensional (3D) graphene aerogel (GA) structure (NiHCF/GA), through which we have derived OER active FeNi-P/GA catalyst by heating with the phosphide source. Structural characterization data disclosed that the NiHCF derived FeNi-P particles were uniformly distributed in the 3D GA network. The obtained FeNi-P/GA catalyst exhibits precursor ([K3 Fe(CN)6 ] and NiCl2 ) concentration-dependent electrocatalytic activity towards OER. Linear sweep voltammetry (LSV) study shows OER on the optimized FeNi-P/GA catalyst surface commenced at 1.46 V vs . RHE and demands only 280 mV overpotential to achieve the benchmark current density of 10 mA.cm −2 . Also, the FeNi-P/GA catalyst displayed a Tafel slope of 43 mV.dec −1, suggesting its superior OER performance in alkaline condition. Highlights: Graphene aerogel (GA) supported FeNi-P nanoparticles were derived from Electroactive nickel hexacyanoferrate. FeNi-P/GA exhibited superior performance towards water oxidation reaction. The developed method is more effective for the preparation of other metal hexacyanoferrate derived catalysts.